OPTIMASI PRODUKSI ENERGI SURYA DARI DESAIN PEMBANGKIT TENAGA SURYA DI ATAP STT-PLN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
In the future, the greater of the consumption energy, the use of diverse energy sources can not be avoided. Therefore, assessment of the various sources of energy technologies continue to be developed. Photovoltaic technologies that convert solar energy directly into electrical energy using semiconductor devices called solar cells. Solar energy apart easily obtained from natural, environmentally friendly too which does not produce CO2 emissions to become a mainstay in the world of technology. The problem is how to use solar panels to get optimal production of electrical energy as solar panels are generally placed at a certain position without change.The design of this solar cells, built at roof over an area of 50 m2 has a power output of 6 kWp with the installation of solar panels with a slope of 6 degrees which can produce electrical energy about 10,006.7 kWh per year. It is connected to the grid (grid connected) without battery. For the manufacture of solar investment of Rp. 445.453.328, - where the investment already include the cost of maintenance and life cycle costs over 25 years.